Protection of the constitution and fundamental rights under the martial law in Pakistan, 1958-1962 - Patwari, A. B. M. Mafizul Islam (Dhaka, Bangladesh : University of Dhaka, 1988)
Includes references to former East Pakistan, now Bangladesh.
Revision of the author's thesis (M. Phil.--University of Rajshahi, 1980)
Includes index.
Bibliography: p. [202]-213.
Keywords: Martial law -- Pakistan -- History; Civil rights -- Pakistan -- History; Civil rights -- Bangladesh -- History